Land concentration in South Africa: Black farm dwellers caught in the ‘claws’ of wildlife production and private luxury tourism in the Eastern Cape - (:unkn) unknown (My University, 2015)
The rapid expansion of wildlife production has significantly changed the social and spatial landscape of South Africa’s Eastern Cape through the merging of white-owned commercial farms, replacing many of its agriculture activities and displacing most of the black families who livedand worked on them. The article looks at the example of luxury private game reserves, marketed as “natural” areas, devoid of traces of human existence, to wealthy international tourists enticed by descriptions of the ‘African bush experience’ in exclusive 4- or 5-star accommodations. Itanalyses the land and labour relations that, historically and currently, are the backdrop to this major land use change, food insecurity and other social impacts on black South African farm dweller families, as well as their future perspectives after being uprooted from the farms. This is part of a broader trend of growing land concentration in post-apartheid South Africa, facilitated by the neoliberal environment, globalisation and 20 years of failed market-led land reform.
Keywords: African Research